2010
DOI: 10.1124/jpet.110.172742
|View full text |Cite
|
Sign up to set email alerts
|

The Novel Pyrrolidine Nor-Lobelane Analog UKCP-110 [cis-2,5-di-(2-phenethyl)-pyrrolidine hydrochloride] Inhibits VMAT2 Function, Methamphetamine-Evoked Dopamine Release, and Methamphetamine Self-Administration in Rats

Abstract: Both lobeline and lobelane attenuate methamphetamine selfadministration in rats by decreasing methamphetamine-induced dopamine release via interaction with vesicular monoamine transporter-2 (VMAT2). A novel derivative of nor-lobelane, cis-2,5-di-(2-phenethyl)-pyrrolidine hydrochloride (UKCP-110), and its transisomers, (2R,5R)-trans-di-(2-phenethyl)-pyrrolidine hydrochloride (UKCP-111) and (2S,5S)-trans-di-(2-phenethyl)-pyrrolidine hydrochloride (UKCP-112), were evaluated for inhibition of [ It is noteworthy th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 26 publications
4
25
0
Order By: Relevance
“…Through an interaction with VMAT2, lobeline inhibits the neurochemical and behavioral effects of methamphetamine (Teng et al, 1997(Teng et al, , 1998Harrod et al, 2001;Miller et al, 2001;Dwoskin and Crooks, 2002;Nickell et al, 2010). Lobelane, a lobeline analog with greater selectivity for VMAT2, decreased both methamphetamineevoked DA release (IC 50 ϭ 0.65 M; I max ϭ 73.2%; same experimental conditions as the current work) and methamphetamine self-administration (Zheng et al, 2005a;Neugebauer et al, 2007;Beckmann et al, 2010;Nickell et al, 2010Nickell et al, , 2011. Unfortunately, further development of lobelane as an effective pharmacotherapy was hindered by unacceptable drug-likeness properties.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Through an interaction with VMAT2, lobeline inhibits the neurochemical and behavioral effects of methamphetamine (Teng et al, 1997(Teng et al, , 1998Harrod et al, 2001;Miller et al, 2001;Dwoskin and Crooks, 2002;Nickell et al, 2010). Lobelane, a lobeline analog with greater selectivity for VMAT2, decreased both methamphetamineevoked DA release (IC 50 ϭ 0.65 M; I max ϭ 73.2%; same experimental conditions as the current work) and methamphetamine self-administration (Zheng et al, 2005a;Neugebauer et al, 2007;Beckmann et al, 2010;Nickell et al, 2010Nickell et al, , 2011. Unfortunately, further development of lobelane as an effective pharmacotherapy was hindered by unacceptable drug-likeness properties.…”
Section: Discussionmentioning
confidence: 99%
“…However, the order of potency for inhibition of VMAT2 function (GZ-793A ϭ GZ-794A Ͼ GZ-796A) was different from the order of potency for inhibition of methamphetamine-evoked DA release (GZ-794A Ͼ GZ-796A Ͼ GZ-793A). Furthermore, correlation analysis with a limited number of structurally related compounds [GZ-793A, GZ-794A, GZ-796, lobelane, lobeline, mesotransdiene, cis-2,5-di-(2-phenethyl)-pyrrolidine hydrochloride (UKCP-110), and (3Z,5Z)-3,5-bis(2,4-dichlorobenzylidene)-1-methylpiperidine (UKMH-106)] for which data are available from both assays (current study ;Miller et al, 2001Miller et al, , 2004Beckmann et al, 2010;Nickell et al, 2010;Horton et al, 2011) reveal a lack of correlation between affinity for the inhibition of DA uptake at VMAT2 and the ability to inhibit methamphetamineevoked DA release. There are several alternative explanations for this lack of correlation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considerable attention has been given to positive rewarding effects associated with MA addiction (Beckmann et al, 2010;Horton et al, 2011;Kamens et al, 2005;Mahler et al, 2013;Meyer et al, 2011;Mizoguchi et al, 2004;Shabani et al, 2011Shabani et al, , 2012aWheeler et al, 2009), whereas aversive effects that could limit intake have been given less consideration (Harrod et al, 2010;Pringle et al, 2008;Shabani et al, 2011Shabani et al, , 2012bWheeler et al, 2009). Greater Figure 3 (a) Methamphetamine (MA) consumption differs by Taar1 genotype.…”
Section: Discussionmentioning
confidence: 99%
“…Its main alkaloid is the lobeline, which due to its stimulating effect on the respiratory centre is used in cases of gas and narcotic poisoning [12,13]. Recently, the species has come into the limelight due to research on CNS, drug abuse and multidrug resistance [14][15][16][17][18][19]. Several studies have shown that lobeline improves memory in rodents, probably due to its involvement in cholinergic mechanisms of neurotransmission.…”
Section: Introductionmentioning
confidence: 99%